Characterization Of Secondary Metabolites From The Rhizome Of Cynara Scolymus And Their Antioxidant Properties. Issue 12 (31st May 2021) - Lee, Chia-Lin; Liao, Kuo-Chen; Chen, Chien-Chih; Lin, Yen-An; Wu, Tung-Ying; Jhan, Yun-Lian; Chen, Chao-Jung; Yang, Juan-Cheng; Wu, Yang-Chang
Abstract: The aerial portions of Cynara scolymus commonly have been eaten as vegetables or functional foods by the people lived in Mediterranean region. In preliminary antioxidant screening, the rhizome portions (CSR) of this species showed better potential than leaves ones. However, neither phytochemical nor pharmacology studies of CSR have been reported to date. The purpose of this research was to identify the active components from CSR through bioassay-guided fractionation. The antioxidant properties of secondary metabolites 1 –9 were evaluated in this investigation. Compounds 4 –6, 8, and 9 showed antioxidant activities based on DPPH free radical scavenging activity with IC50 values of 22.91–147.21 μM. Besides, compound 8 significantly and dose-dependently reduced H2 O2 -induced ROS levels in keratinocyte HaCaT cells without cytotoxicity toward HaCaT. Overall, our studies demonstrated the rhizome of C. scolymus could be used as a new natural antioxidant like the edible aerial portions and phenolic compounds are the active components. Graphical Abstract: